Diagnoctic Value of Circulating Cell-Free DNA in Lung Cancer Detection: A Systematic Review - Melly Miranda; Tjandra Yoga Aditama; Insan Sosiawan; Andika Chandra Putra; Thabina Anindya Rizaldi; Mishael Enoch Stephen (Greenation Publisher & Yayasan Global Research National, 2026)
Lung cancer remains a leading cause of cancer-related mortality worldwide, with poor prognosis largely due to late-stage diagnosis. Early detection is essential to improve survival outcomes; however, current screening methods have limitations, including false-positive results and radiation exposure. This study aimed to evaluate the diagnostic value of circulating cell-free DNA as a minimally invasive biomarker for lung cancer detection through liquid biopsy. This systematic review was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines using the Population, Intervention, Comparison, and Outcome framework. Literature searches were performed up to March 2026 in several databases. A total of 265 records were identified, of which three studies met the inclusion criteria. The findings demonstrated that circulating cell-free DNA-based approaches, including mutation profiling and deoxyribonucleic acid methylation analysis, showed clinically meaningful diagnostic performance, with sensitivity ranging from 67% to 87.8% and specificity from 73% to 96%. Methylation-based methods demonstrated higher sensitivity and the ability to differentiate lung cancer from non-malignant pulmonary diseases. Overall, circulating cell-free DNA analysis shows strong potential as a minimally invasive tool for lung cancer detection.